PROBLEMS OF ELECTRONIC CRIMINAL PROCEDURE IN KAZAKHSTAN AND COMPARATIVE ANALYSIS OF FOREIGN DIGITAL INVESTIGATION MODELS (Journal of actual problems of jurisprudence, 2025)
The digitalization of criminal procedure has become a key vector in the modernization of law enforcement systems. The use of ICT accelerates pre-trial investigations and enhances data-processing accuracy. In the Republic of Kazakhstan, the basic infrastructure for electronic criminal procedure, including online services, has already been established; however, existing regulations and the practical functioning of electronic systems reveal systemic limitations that impede the development of a fully integrated digital investigation model. The purpose of this study is to provide a comprehensive assessment of the current state and prospects for the development of electronic criminal procedure in Kazakhstan. The research includes identifying regulatory and practical challenges, analysing conflicts between the Criminal Procedure Code of the Republic of Kazakhstan and subordinate acts, conducting a comparative review of foreign models (CMS, e-File, eDiscovery), and formulating proposals for adapting effective international practices.The methodological framework relies on legislative analysis, an assessment of digital infrastructure, and the study of international experience. Systematization and comparative legal methods were applied, enabling the identification of seven key issues affecting the effectiveness of electronic investigations.The analysis revealed the absence of clear ICT procedural regulations, inconsistencies between the CPC and the Prosecutor General’s Order No. 2, weak integration of the “E-QI” and “Qamqor” systems with the databases of the Committee on Legal Statistics, and the lack of a defined liability mechanism for breaches of confidentiality in the “Jaria Sector.” Additional gaps were identified in the regulation of remote investigative actions, the handling of physical evidence, and the determination of criteria limiting the use of electronic formats. The scholarly value lies in formulating a systemic conceptual framework based on the identification of seven structural barriers. This integrated approach, combining legal, technological, and organizational dimensions, fills a methodological gap in national academic discourse.The practical significance is reflected in the proposed solutions designed for implementation in regulatory and technological environments: unifying the regulatory framework (a supplementary CPC chapter), establishing an integration bus and Data Hub, introducing a QR-based evidence management module, and creating a liability mechanism for confidentiality breaches within the “Jaria Sector.” These measures are expected to enhance investigative efficiency and support the development of a full-fledged electronic ecosystem for criminal procedure in Kazakhstan.Keywords: electronic criminal procedure, digital pre-trial investigation, chain of custody, information system integration.